2016
DOI: 10.1038/srep32152
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the ESIPT Process for a New Natural Product Quercetin

Abstract: The investigation of excited-state intramolecular proton transfer (ESIPT) has been carried out via the density functional theory (DFT) and the time-dependent density functional theory (TDDFT) method for natural product quercetin in dichloromethane (DCM) solvent. For distinguishing different types of intramolecular interaction, the reduced density gradient (RDG) function also has been used. In this study, we have clearly clarified the viewpoint that two kinds of tautomeric forms (K1, K2)originated from ESIPT pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…The information of wave function has been calculated and analyzed for compounds 1 and 3 in different electronic states via DFT and TDDFT methods, respectively. Most of contemporary researchers have extensively adopted these theoretical methods to investigate photophysical and photochemical reaction mechanisms of organic molecules in the past [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The whole computational processes are based on the Gaussian 09 program [23].…”
mentioning
confidence: 99%
“…The information of wave function has been calculated and analyzed for compounds 1 and 3 in different electronic states via DFT and TDDFT methods, respectively. Most of contemporary researchers have extensively adopted these theoretical methods to investigate photophysical and photochemical reaction mechanisms of organic molecules in the past [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The whole computational processes are based on the Gaussian 09 program [23].…”
mentioning
confidence: 99%
“…Then, the excited keto tautomer deactivates radiatively and goes through a reverse ESIPT, producing ground-state enol form again. Many previous works demonstrated that hydrogen bond plays a significant role in the ESIPT process [39][40][41][42], and thus, it is significantly important to study the hydrogen bond behavior in excited state and its effect on ESIPT process, which not only sheds light on the nature of ESIPT, but also provides constructive ideas for designing and tuning desired fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Most aprotic solvents shift the equilibrium toward the keto tautomer by increasing the polarity. The polar protic solvents can form intermolecular hydrogen bonds resulting in a stabilized keto form [19][20][21][22]; (iv) the planarity of 2-hydroxy species is essential to intramolecular hydrogen bonding and proton transfer reactions [23][24][25]; (v) last but not least, is the temperature influences on tautomerization and ESIPT efficiency. Several useful papers provide a very insightful investigation of low temperature spectral behavior [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%